Nanopore sequencing reveals genomic map of CTX-M-type extended-spectrum β-lactamases carried by Escherichia coli strains isolated from blue mussels (Mytilus edulis) in Norway - Didrik H. Grevskott; Francisco Salvà-Serra; Edward R. B. Moore; Nachiket P. Marathe (BMC Microbiology, 2020)
Abstract Background Environmental surveillance of antibiotic resistance can contribute towards better understanding and management of human and environmental health. This study applied a combination of long-read Oxford Nanopore MinION and short-read Illumina MiSeq-based sequencing to obtain closed complete genome sequences of two CTX-M-producing multidrug-resistant Escherichia coli strains isolated from blue mussels (Mytilus edulis) in Norway, in order to understand the potential for mobility of the detected antibiotic resistance genes (ARGs). Results The complete genome sequence of strain 631 (E. coli sequence type 38) was assembled into a circular chromosome of 5.19 Mb and five plasmids (between 98 kb and 5 kb). The majority of ARGs cluster in close proximity to each other on the chromosome within two separate multidrug-resistance determining regions (MDRs), each flanked by IS26 transposases. MDR-1 carries bla TEM-1, tmrB, aac(3)-IId, aadA5, mph(A), mrx, sul1, qacEΔ1 and dfrA17; while MDR-2 harbors aph(3″)-Ib, aph(6)-Id, bla TEM-1, catA1, tet(D) and sul2. Four identical chromosomal copies of bla CTX-M-14 are located outside these regions, flanked by ISEc9 transposases. Strain 1500 (E. coli sequence type 191) exhibited a circular chromosome of 4.73 Mb and two plasmids (91 kb and 4 kb). The 91 kb conjugative plasmid belonging to IncI1 group carries bla CTX-M-15 and bla TEM-1 genes. Conclusion This study confirms the efficacy of combining Nanopore long-read and Illumina short-read sequencing for determining complete bacterial genome sequences, enabling detection and characterization of clinically important ARGs in the marine environment in Norway, with potential for further dissemination. It also highlights the need for environmental surveillance of antibiotic resistance in low prevalence settings like Norway.